Chersine Merrem, 1820 and Chersina Gray, 1831: a nomenclatural survey - Bour, Roger; Ohler, Annemarie (Zootaxa, 2008)
In the tenth Edition of his ‘Systema Naturae’, Carolus Linnaeus presented among the species of the genus Testudo (including all the turtles and tortoises, thus corresponding to the present order of Chelonians) the species Testudo graeca (Linnaeus 1758). The reference was the description and the plate published by George Edwards (1751) of a tortoise from North Africa, more precisely from the old fort of Santa-Cruz (presently Djebel Murdjadjo or “pic de l’Aïdour” 35°42’N, 0°45’W, Oran, Algeria). Several hypotheses tried to explain Linnaeus’s choice of the name graeca, one proposing that the species is the tortoise of the old Greek authors. Nevertheless, since 1758, the identity of Testudo graeca is rather well established, with a precise type locality, although the pictured holotype is lost. Testudo graeca Linnaeus, 1758 is the type species of Testudo Linnaeus, 1758 by subsequent designation of Bell (1828).